2006
DOI: 10.1007/s10570-006-9052-5
|View full text |Cite
|
Sign up to set email alerts
|

Visualisation of the fibrillar and pore morphology of cellulosic fibres applying transmission electron microscopy

Abstract: Applying transmission electron microscopy (TEM) on ultra-thin cross-sections of fibres, the main characteristics of the internal morphology of cotton and the main man-made cellulosic fibres (modal, viscose and lyocell) could be visualised. To obtain an appropriate contrast for TEM, isoprene was polymerised into the swollen fibres after a stepwise solvent exchange from water to acetone. The included polymer is stainable with osmium tetraoxide. Significant differences in distribution of pore sizes and pore arran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Comfort is also associated with the interaction of water with cellulose at the molecular level [5], which induces a strong exothermic sorption response, with an equivalent endothermic response induced as water is evaporated [6,7]. The nanoscale textures created in cellulosic fibres during regeneration have a high liquid holding capacity, as pore spaces are opened between cellulose polymer domains [8][9][10]. The rapid uptake of water into the fibre internal volume is ideal for technical applications where high absorbency is required [11].…”
Section: Introductionmentioning
confidence: 99%
“…Comfort is also associated with the interaction of water with cellulose at the molecular level [5], which induces a strong exothermic sorption response, with an equivalent endothermic response induced as water is evaporated [6,7]. The nanoscale textures created in cellulosic fibres during regeneration have a high liquid holding capacity, as pore spaces are opened between cellulose polymer domains [8][9][10]. The rapid uptake of water into the fibre internal volume is ideal for technical applications where high absorbency is required [11].…”
Section: Introductionmentioning
confidence: 99%
“…Some pores and defects could be also present in the amorphous regions. Abu-Rous et al (2006) showed that Lyocell fibres contain only nanopores in the core of the fibre and a very porous skin layer. Schurz et al (1995) proposed a structural model for fibres spun from cellulose-NMMO-water solutions.…”
mentioning
confidence: 99%
“…Although the treatment decreased the number of nanoparticles on the cotton fabrics, there were still a little bit of nanoparticles dispersed on the surface of the cotton, which was attributed to the chemical structure and framework structure of the cotton fabrics. Holes (50–200 nm) on the surface of the cotton fibers26 could make the nanoparticles penetrate into themselves depending on the osmotic pressures. Besides, cotton was a natural fiber consisting of cellulose with 1,4‐ D ‐glucosepyranose as its repeating units 27.…”
Section: Resultsmentioning
confidence: 99%